PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGAN MEDIA DART BOARD UNTUK MENINGKATKAN HASIL BELAJAR KIMIA Di KELAS XI IPA 1 SMA NEGERI 9 KOTA BENGKULU TAHUN AJARAN 2016/2017 - Defrilina Sri Eka Wulandari; Amrul Bahar; Elvinawati Elvinawati (ALOTROP, 2018)
[THE  APPLICATION OF INQUIRY LEARNING MODEL WITH  DART BOARDMEDIA TO IMPROVE THE STUDIED RESULTS OF  CHEMISTRY IN CLASS XI IPA 1 SMA NEGERI 9 CITY OF BENGKULU  AT 2016/2017 ACADEMIC YEAR]  This research aims to improve the learning outcomes and student activity model of learning by implementing a inkuiri dart board with media in class XI IPA 1 SMA Negeri 9 Bengkulu city at 2016/2017. Academic year. This research is a class action research. This research was conducted in three cycles consisting of 4 stages each namely planning, implementation, observation, and reflection. The subject of this research is the whole grade X IPA 1 SMA N 9 Bengkulu city on 2016/2017 academic year. From the results, it can be concluded that the process of learning to apply inquiry learning models by using a Dart Board media proved can improve the activity and outcomes of study chemistry grade XI IPA 1 SMA Negeri 9  Bengkulu city on 2016/2017 academic year. It can be seen from the average value of students in Ist cycle are 61.61, classical absorption 77.02% and learning of classical completeness at 19.35%..In Iind Cycle obtained an average score of students amounted to 71.29; absorption of conventional 79.21% and  completeness studied conventional 35.48%. In IIIth cycle received an average rating of students at 84.51; absorption of conventional 84.51% and  completeness  studied classical 90.32%.. For the entire sequence of an increase in the activity of the students which can be seen from the mean value – 1st cycle averages of 22.5, 2nd cycle at 25; and in 3th cycle at 29.